P1714 When the mechanism of mitral regurgitation is unclear, 3D Trans-esophageal echocardiography is the solution. (17th January 2020) - Thabet, N; Labib, D; Nagy, S; Mahmoud-Elsayed, H
Abstract: Introduction: Assessment of mitral regurgitation (MR) mechanism is not always easy and may require advanced imaging techniques. A 28-year-old male presented with significant MR three years following surgical mitral valve repair for severe MR due to mitral valve prolapse. During surgery, he underwent artificial chordal implantation on A2 scallop and Gore-Tex posterior band annuloplasty. Early post-operative transthoracic echocardiography (TTE) showed mild to moderate eccentric, posteriorly directed MR of unknown mechanism. Since the patient was asymptomatic, only regular follow-up was advised. He missed his follow-up for three years after which presented complaining of exertional dyspnea NYHA class II. TTE showed dilated left ventricular dimensions with moderate to severe MR of unknown mechanism. 2D trans-esophageal echocardiography (TEE) (figure 1, panel A& B) showed severe, posteriorly directed mitral regurgitation, with a mass (arrow head) at the level of the mitral annulus. 3D TEE (figure 1, panel C, 3D zoom mode and panel D, true view mode) showed dehiscence (arrow head) of the annuloplasty band from the posterior mitral annulus with a wide gap measuring 83 mm² in 3D planimetred area. The patient was referred for re-do surgery. Conclusion: 3D TEE has a great added value in elucidating the mechanism of MR in obscure cases and guiding the proper management strategy.